Between Affect and Structure: Shame, Mobility, and the Novel Form - Cathelain, Neela. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of English.; Advisors: Lee Edelman, and Alexis Tadié.; Committee: Jess Keiser, Sonia Hofkosh, Vanessa Guignery, and Kerry-Jane Wallart.; Keywords: Literature, American literature, and English literature.